2011
DOI: 10.17221/112/2011-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance to Fusarium head blight in wheat using different sources of inoculum

Abstract: Abstract:The response of four winter wheat cultivars, differing in resistance to Fusarium head blight (FHB), to spray inoculation with four selected Fusarium graminearum isolates, mixture of these isolates and frequently used F. culmorum isolate B was studied in five field and glasshouse experiments during 2008-2010. Analyses of variance showed highly significant main and interaction effects of cultivar, inoculum source and environment (year-trial) on all five examined traits indicative of disease severity, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several earlier pieces of research also confirmed the existence of genotypic variations among wheat genotypes for agronomic parameters at various experimental conditions for a number of reasons (Purchase et al 2000;Wiśniewska et al 2004;Buerstmayr et al 2008;Šíp et al 2011;Cazal-Martínez et al 2020). Furthermore, tested genotypes produce a comparatively higher overall mean yield at Bonke and Chencha than others.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Several earlier pieces of research also confirmed the existence of genotypic variations among wheat genotypes for agronomic parameters at various experimental conditions for a number of reasons (Purchase et al 2000;Wiśniewska et al 2004;Buerstmayr et al 2008;Šíp et al 2011;Cazal-Martínez et al 2020). Furthermore, tested genotypes produce a comparatively higher overall mean yield at Bonke and Chencha than others.…”
Section: Discussionmentioning
confidence: 59%
“…The results pointed out the inconsistency in genotypes' response to FHB, and a single genotype could not be advised for cultivation across environments. In wheat resistance breeding for FHB, tests of genotype performance across a broad range of agro-ecologies (environments) are considered to lessen the influence of GEI, ensuring that the nominated genotypes keep stable resistance against FHB coupled with high-yield performance across many environments (Buerstmayr et al 2008;Šíp et al 2011;Beres et al 2018;Cazal-Martínez et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, Šíp et al. (2011) reported all isolates and the mixture of F. graminearum isolates detected the lowest values of all traits in the moderately resistant cultivar; however, there were obvious differences among isolates in the ability to detect significant differences among varieties that differ greatly in FHB resistance. On the other hand, Goswami and Kistler (2005) reported significant variation among the strains of F. graminearum species in their ability to cause FHB on wheat.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, Goswami and Kistler (2005) reported significant variation among the strains of F. graminearum species in their ability to cause FHB on wheat. The carefully selected mixture of isolates with varying properties is an alternative to the parallel use of specific isolates, which could bring tests closer to natural infections while lowering costs (Šíp et al., 2011). From our findings, no complete resistance reaction was observed in any of the varieties evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Because field trials of woody ornamentals require a great deal of space and effort, a screening method in a seedling stage is beneficial. Examples of the use of such screening are found in several crops, such as maize (Mesterhazy, Lemmens, & Reis, 2012), wheat (Sip, Chrpova, & Stockova, 2011) and also in some ornamentals such as roses (Leus, Huylenbroeck, Bockstaele, & Höfte, 2008), Anthurium (Elibox & Umaharan, 2008) and Rhododendron (Van Huylenbroeck, Calsyn, Keyser, & Luypaert, 2015).…”
Section: Discussionmentioning
confidence: 99%